Factors influencing the formation of feeling of familiarity - Ευκλείδη, Αναστασία; Πανταζή, Μαρία; Γιαζκουλίδου, Αικατερίνη (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF